Fat and Bone: An Odd Couple - Kremer, Richard; Gilsanz, Vicente (Frontiers in Endocrinology, 2016)
In this review, we will first discuss the concept of bone strength and introduce how fat at different locations, including the bone marrow, directly or indirectly regulates bone turnover. We will then review the current literature supporting the mechanistic relationship between marrow fat and bone and our understanding of the relationship between body fat, body weight and bone with emphasis on its hormonal regulation. Finally, we will briefly discuss the importance and challenges of accurately measuring the fat compartments using non-invasive methods. This review highlights the complex relationship between fat and bone and how these new concepts will impact on our diagnostic and therapeutic approaches in the very near future.